Dengue epidemic during the COVID-19 pandemic in the State of Sergipe: a concern for health services and a warning to intensify prevention and control measures (Research, Society and Development, 2021)
The Pan American Health Organization (PAHO) has guided the importance of maintaining measures and actions to prevent, detect and treat vector-borne diseases during the COVID-19 pandemic, since the combined impact of these diseases can have devastating consequences for the population, above all, vulnerable people such as children, the elderly and those diagnosed with cardiovascular diseases. Thus, this letter to the editor is a reflection to alert the scientific community, professionals, and managers about the impact of dengue epidemics during the COVID-19 pandemic. The state of Sergipe, located in the Northeast of Brazil, has a high level of building infestation by the Aedes aegypti mosquito and is endemic for dengue. Other Brazilian states also have the same epidemiological situation. Thus, it is important that control measures be intensified to continue dengue prevention. The situation may be aggravating in the coming years in terms of incidence and morbidity and mortality.